2015
DOI: 10.1104/pp.15.01776
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-Regulated Glutaredoxins Control Arabidopsis Primary Root Growth

Abstract: Nitrogen is an essential soil nutrient for plants, and lack of nitrogen commonly limits plant growth. Soil nitrogen is typically available to plants in two inorganic forms: nitrate and ammonium. To better understand how nitrate and ammonium differentially affect plant metabolism and development, we performed transcriptional profiling of the shoots of ammoniumsupplied and nitrate-supplied Arabidopsis (Arabidopsis thaliana) plants. Seven genes encoding class III glutaredoxins were found to be strongly and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 69 publications
(95 reference statements)
2
66
0
Order By: Relevance
“…Also three members of the ROXY family (also known as GRX5, GRX8 and GRX11 ), are all downregulated. They are involved in cell redox homeostasis, and are all induced by nitrate (Patterson et al, 2016). Conversely, three members of the FE-UPTAKE-INDUCING PEPTIDE family, IRONMAN 1, IRONMAN 2 and IRONMAN 3 , were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Also three members of the ROXY family (also known as GRX5, GRX8 and GRX11 ), are all downregulated. They are involved in cell redox homeostasis, and are all induced by nitrate (Patterson et al, 2016). Conversely, three members of the FE-UPTAKE-INDUCING PEPTIDE family, IRONMAN 1, IRONMAN 2 and IRONMAN 3 , were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…+S has the opposite effect. A similar RSA pattern has been observed for Arabidopsis nitrogen (N) nutrition (Patterson et al ., ) where it has been interpreted as a nutrient foraging mechanism that permits seedlings to probe deeper soil layers where nitrate accumulates (Gruber et al ., ). Plant response to sulfate is predicted to be similar to nitrate because both anions are highly soluble and settle deeper in soil (Gruber et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard it is important to note a recent study by Patterson et al . () who identified glutaredoxins (GRXs) that regulate RSA response to N‐limitation. GRXs are redox‐active proteins that were first characterized as using GSH as a reductant.…”
Section: Discussionmentioning
confidence: 99%
“…Two forms of GRX (spots 13 and 55), electron transfer flavoprotein subunit beta protein (spot 33) and UPF0235 protein C15orf40 homolog isoform X3 (spot 39) were expressed uniquely in germinating somatic embryos. GRX are known to be involved in plant responses to growth regulators like auxin, cytokinin and GA, which are necessary for growth and development of root and shoots (Eckardt , Kereamy et al , Patterson et al ). Kereamy et al () reported that the overexpression of GRX results in increased biosynthesis of GA and cytokinin, leading to the formation of shoots in rice whereas Patterson et al () reported that class 3 GRX plays a significant role in the root hormone regulation in Arabidopsis thaliana .…”
Section: Discussionmentioning
confidence: 99%